ANALISIS PENGARUH TEMPAT PENYIMPANAN TERHADAP BESARNYA KANDUNGAN LOGAM Pb DAN Zn DALAM DAGING KORNET HABIS PAKAI KEMASAN KALENG - Syakri, Syamsuri; Mursyid, A. Mumtihanah (Fakultas Farmasi UMI, 2013)
This research was conducted with the aim to investigate the influence of storage on the size of the metal content of Pb and Zn to quality consumable products corned beef cans obtained from a grocery store or supermarket, and to determine the ratio between the metals Pb and Zn results, with SK. DG BPOM No.03725/ B / SK / VII / 89 maximum of metal contamination in food. In this study, the sampling method used is the method of random sampling in which sampling method from a single population and each population has an equal chance to be selected as sample. Analysis of heavy metal Pb in all samples showed uptake results ranged from 0.0000 to 0.0005, or may be heavy metal pollution Pb is very small. Total Pb (lead) was much less after storage in the refrigerator for 1 day of corned beef packaging consumables, it is possible the influence of the storage temperature. Analysis of Zn metal in the samples showed varying results, it is because the meat itself was contained zinc metal content. Total Zn (Zinc) also was less after storage in the refrigerator for 1 day of corned beef packaging consumables, it is possible the influence of storage temperature affect the metal content. Analysis of Pb (lead) and Zn (zinc) in a sample of corned beef canned consumables still below the threshold set by decree. SNI No. 7387:2009 above the maximum limit of metal contamination in food, so the packaging corned beef is still suitable for consumption and circulated in the market.Key words: Corned Meat Packaging Cans, Metal Pb, Zn Metal, Storage